14. A FULLY AUTOMATED INSTRUMENT FOR PREIMPLANTATION GENETIC TESTING (PGT-A) LIBRARY PREPARATION. (August 2019) - Schneider, L.; Cui, F.; Brodsky, A.; Fraser, M.; Toloue, M.; Tripathi, A.
Abstract : Introduction: Technology used in preimplantation genetic testing for aneuploidy (PGT-A) has rapidly evolved since its introduction in 1990. The most commonly used methods use Next Generation Sequencing (NGS) for complete genomic analysis. One example is the PG-Seq™ kit (PerkinElmer), which begins with a sample of embryo biopsy cells and ends with a full analysis of the DNA library sequence. NGS sample preparation is a laborious, hands-on, and time-intensive process. We have developed a fully automated microfluidic platform to perform library preparation for the PG-Seq kit workflow. This instrument not only reduces the "hands on" time; it also helps to standardize the DNA library preparation through removing all manual pipetting handling and ensuring precise and consistent results between sample preparations, even between NGS runs. Materials & Methods: The main objective of this study was to demonstrate the performance of a specifically designed automation instrument for single sample library preparation as is used in the PG-Seq kit for NGS. The NEXTFLEX® Rapid XP DNA-Seq Kit from Bioo Scientific (a PerkinElmer Company) was used to optimize this platform, following standard manufacturer's instructions. The three main components of this assay are (1) Fragmentation, End-Repair & Adenylation, (2) Adapter Ligation, and (3) PCR Amplification. The enzymatic fragmentation of the input DNA is a crucial component of this assay as this step is necessary for the PG-Seq™ kit following whole genome amplification. The representative input DNA used in this specific study was 180 ng of Lambda DNA from New England Biolabs. This kit was also tested off-device using fully manual preparation as a control and both on-device and off-device samples were evaluated using the NanoDrop 1000 Spectrophotometer and Agilent Bioanalyzer 2100 (DNA 1000 Kit) for DNA library concentration, purity, and size analysis. Results: The total yield of prepared DNA library using the instrument is around 50% of the off-device, manual testing. More specifically, the off-device, manual tests resulted in 739.1 ± 44.8 ng of DNA in a 20 μL sample, while the most recent on-device testing produced 415.1 ± 54.1 ng of DNA in a 20 μL sample. The average fragment sizes in these libraries is between 300 and 400 base pairs. As performing this assay on this instrument is further optimized, it is anticipated that this library yield will increase. Additionally, this study shows a significant decrease in the amount of hands-on time needed for researchers to run the NEXTFLEX® Rapid XP DNA-Seq Kit from ∼2.5 hours to less than 30 minutes required to load reagents into their appropriate wells before starting the instrument. This instrument has also been optimized for additional DNA-Seq kits and, when launched, will accommodate even more protocols offering a flexible automation system. Conclusions: Overall, this instrument is a hands-free device for NGS sample library preparation that automates the PG-Seq kit library preparation. In time, this technology will be combined with PG-Seq Whole Genome Amplification, providing a fully automated system that can be used for routine PGT-A.